La mondialisation par le petit bout de la lorgnette - Iteanu, André (Anthropologica, 2022)
In this article, globalization is treated as an ideology which admits two principal versions. The first, mainly Western, poses that the planet is gradually invaded by a single mode of life; the second, rather from the periphery, that globalization will one day reach one's own village or city and it will entice major changes. The first of these alternatives supposes a natural continuity across all societies and privileges relations to things. The second stresses relations between people as inseparable from relations to things and is often represented as a relation to one's own ancestors. Surprisingly, however, this is not a marginal view. When examining some examples of "modern" relations, such as economic aid between states or immigration, one finds elements of the same concern for relation with a world of "the beyond." The persistence of this archaic feature in the mists of "modernity" does, however, neither reflect a universal existential fright of death, nor the quaint character of certain societies, but rather that, in the dialogue between these societies and the West, the latter sees itself—and is therefore seen by others—as a sort of paradise on earth.